К вопросу о значении энклитического местоимениа -пу в угаритском языке - Шифман, И. Ш.
Šifman, I. S., The Problem of the Meaning of the Enclitic Pronoun -пу in Ugarit; engl. Résumé S. 277; plural, not dual.